2014
DOI: 10.4103/0975-7406.137429
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the frictional resistance between archwire and different bracket system: An in vitro study

Abstract: Background and Objectives:The purpose of this study is to evaluate the frictional resistance generated by conventional stainless steel, radiance ceramic bracket, self-ligating and composite brackets using a 0.019 × 0.025 stainless steel straight length wires in a 022 slot and to select brackets based on their frictional characteristic.Methodology:In order to conduct this study, four different types of bracket system were selected of the mclaughlin-bennet-trevesi (MBT) discipline. They are Group 1 - stainless s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
2
9
0
1
Order By: Relevance
“…In the present study, we observed that in sliding mechanics, the ceramic bracket presented significantly higher frictional force values than the metal and self-ligating brackets, corroborating the findings in the studies [19][20][21] . One of the causes of high frictional force on ceramic brackets may be due to the scratches found on these brackets, which make sliding difficult, thus increasing the time of orthodontic treatment 22 .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we observed that in sliding mechanics, the ceramic bracket presented significantly higher frictional force values than the metal and self-ligating brackets, corroborating the findings in the studies [19][20][21] . One of the causes of high frictional force on ceramic brackets may be due to the scratches found on these brackets, which make sliding difficult, thus increasing the time of orthodontic treatment 22 .…”
Section: Discussionsupporting
confidence: 92%
“…14a shows that as the coefficient of friction increases from 0.25 to 0.3, transitional locations between partial slip and stick states both move towards the high-tension side (left end), which indicates a decrease in γ and an increase in φ, and thereby reduces the possibility of gross slip between the rope and friction lining and the induced skid accidents. An increase of coefficient of friction induces larger frictional resistance [32,33], and thus causes decreases in the partial slip range, γ. An increase in partial slip range, φ, is probably induced by combined effects of an increase of coefficient of friction and a decrease in the contact pressure in the sticking arc (Fig.…”
Section: Dynamic Contact Characteristics Between the Rope And Frictiomentioning
confidence: 99%
“…But when larger wires are used (like 0.016 × 0.022 and 0.019 × 0.025 nickel-titanium), no differences were found between SLBs and CBs (11). Pillai et al by evaluating frictional resistance generated by conventional stainless steel, radiance ceramic, selfligating and composite brackets concluded that SLB has the least friction among these four types of brackets (12). Leite et al also confirmed this finding in his research in 2014.…”
Section: Resistance To Slidingmentioning
confidence: 85%